Monitoring changes in physical performance with heart rate measures in young soccer players - Buchheit, M.; Simpson, M. B.; Al Haddad, H.; Bourdon, P. C.; Mendez-Villanueva, A. (European Journal of Applied Physiology, 2012)
The aim of the present study was to verify the validity of using exercise heart rate (HRex), HR recovery (HRR) and post-exercise HR variability (HRV) during and after a submaximal running test to predict changes in physical performance over an entire competitive season in highly trained young soccer players. Sixty-five complete data sets were analyzed comparing two consecutive testing sessions (3-4 months apart) collected on 46 players (age 15.1 ± 1.5 years). Physical performance tests included a 5-min run at 9 km h-1 followed by a seated 5-min recovery period to measure HRex, HRR and HRV, a counter movement jump, acceleration and maximal sprinting speed obtained during a 40-m sprint with 10-m splits, repeated-sprint performance and an incremental running test to estimate maximal cardiorespiratory function (end test velocity V Vam-Eval). Possible changes in physical performance were examined for the players presenting a substantial change in HR measures over two consecutive testing sessions (greater than 3, 13 and 10% for HRex, HRR and HRV, respectively). A decrease in HRex or increase in HRV was associated with likely improvements in V Vam-Eval; opposite changes led to unclear changes in V Vam-Eval. Moderate relationships were also found between individual changes in HRR and sprint [r = 0.39, 90% CL (0.07;0.64)] and repeated-sprint performance [r = -0.38 (-0.05;-0.64)]. To conclude, while monitoring HRex and HRV was effective in tracking improvements in V Vam-Eval, changes in HRR were moderately associated with changes in (repeated-)sprint performance. The present data also question the use of HRex and HRV as systematic markers of physical performance decrements in youth soccer players.